2018
DOI: 10.1016/j.progpolymsci.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer nanofibrils: Structure, modeling, preparation, and applications

Abstract: Biopolymer nanofibrils exhibit exceptional mechanical properties with a unique combination of strength and toughness, while also presenting biological functions that interact with the surrounding environment. These features of biopolymer nanofibrils profit from their hierarchical structures that spun angstrom to hundreds of nanometer scales. To maintain these unique structural features and to directly utilize these natural supramolecular assemblies, a variety of new methods have been developed to produce biopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
272
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 357 publications
(273 citation statements)
references
References 592 publications
(873 reference statements)
0
272
0
1
Order By: Relevance
“…Wood aerogels directly obtained from natural wood possessed lower thermal conductivity and density than natural wood and wood waste [46]. It is worth mentioning that, although the thermal insulation performance of wood aerogel was lower than traditional organic materials and cellulose-based aerogel [47], the developed wood aerogel in this study showed much better biocompatibility, biodegradability, and mechanical compressibility, as well as simpler process technology [13,48].…”
Section: Thermal Insulationmentioning
confidence: 77%
“…Wood aerogels directly obtained from natural wood possessed lower thermal conductivity and density than natural wood and wood waste [46]. It is worth mentioning that, although the thermal insulation performance of wood aerogel was lower than traditional organic materials and cellulose-based aerogel [47], the developed wood aerogel in this study showed much better biocompatibility, biodegradability, and mechanical compressibility, as well as simpler process technology [13,48].…”
Section: Thermal Insulationmentioning
confidence: 77%
“…Among nanocelluloses, cellulose nanocrystals (CNC) are stiff nanorods obtained by harsh acid hydrolysis. Thanks to their colloidal properties, high specific surfaces and surface chemistry, CNCs have been the subject of intense research to design innovative biobased materials among which composites, emulsions, foams and hydrogels [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, this conflict does not exist in silk fibers, especially the spider dragline silk and wild silkworm cocoon silks, which feature a unique combination of strength and mechanical toughness. These animal silk fibers resolve the conflict through hierarchical and heterogeneous nanoconfinement, which is defined as optimizing the strength, stiffness, and toughness of materials through confining their building blocks at critical length scales [30,31]. In animal silks, nanoconfinement exists in multiple length scales ( Fig.…”
Section: Discussionmentioning
confidence: 99%